If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -184 = 59 + -12x Reorder the terms: -184 + -3x = 59 + -12x Solving -184 + -3x = 59 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. -184 + -3x + 12x = 59 + -12x + 12x Combine like terms: -3x + 12x = 9x -184 + 9x = 59 + -12x + 12x Combine like terms: -12x + 12x = 0 -184 + 9x = 59 + 0 -184 + 9x = 59 Add '184' to each side of the equation. -184 + 184 + 9x = 59 + 184 Combine like terms: -184 + 184 = 0 0 + 9x = 59 + 184 9x = 59 + 184 Combine like terms: 59 + 184 = 243 9x = 243 Divide each side by '9'. x = 27 Simplifying x = 27
| -56+h-8= | | 2.4=(m+4) | | -7(2+2x)=-70 | | 4x+3(-2x-7)=-7 | | 7a+10a+7a+12a=360 | | -(9-5n)= | | -2(4+m)+6(m-3)=14 | | 4(5x-4)+10=-3 | | 20+8(11-q)=-12 | | 240=126-v | | 6x-12x+9=-27 | | -24-5x=-4(x+5) | | y=101.21x+0.0991 | | 2(3*-0.5+2)-2*-0.5=6*-0.5+5 | | 3(4j-3)8=-1+12j | | 12a+99a=3885 | | -11u-6=3u^2 | | 32-8p=-8(4p+2) | | 7+x=8x-2 | | -7-3v-10+3v=0 | | 5x+48=3x-36 | | 2(3*0.5+2)-2*0.5=6*0.5+5 | | 11x^2y^2=33x^2y | | 3(6s+12-10s-6)=0 | | 3(3n+4)=54+6x | | -5.2+9=-8 | | 22r+10-2= | | (x+7).3=33 | | 15-5x=-40 | | -5.8+9=-8 | | 2(3x+2)-2x=6x+5 | | X-45+45=540 |